Aeromethods in Geocryology - Protaseva,I. V. (1975)
The book discusses the use of aeromethods for studying the development of permafrost soils (rocks) and permafrost phenomena connected with them. Theoretical and methodical conclusions were drawn which can be used as a basis for a further broader adoption of aeromethods into the practice of regional and topical studies of the tendencies in the distribution, composition, structure and properties of permafrost soils. Draft trans. of mono. Aerometody v Geokriologii, Moscow, 1967 196p.